A Novel Energy-Efficiency Social-Inspired Video Sharing Solution in Wireless Networks - Shijie Jia; Youzhong Ma; Yongxin Zhang; Lujie Zhong; Changqiao Xu (International Journal of Distributed Sensor Networks)
Mobile multimedia streaming services provide rich-content visual resources for the mobile users via ubiquitous access to Internet. The video resource sharing focuses on the matching of appropriate resource supplier for the resource requesters and is a key issue for P2P-based video system scalability and user quality of experience. In this context, leveraging social-driven interaction between mobile users enables the discovery of common interests to improve video content sharing efficiency. In this paper, we propose a novel energy-efficiency social-inspired video sharing solution in wireless networks (ESVS). By the analysis of historical request behaviors of users, ESVS designs an estimation method of relationship between videos and groups the videos into a chain-based tree structure. Based on the constructed video tree, ESVS designs a hybrid resource lookup algorithm including push and pull and a communication quality-aware selection strategy of video suppliers, which improves the communication capacities between requesters and suppliers and reduces the network bandwidth consumption. Simulation results also show how ESVS achieves higher resource lookup success rate, lower startup delay, less packet loss rate, and lower maintenance cost than another state-of-the-art solution.